Cytochrome P450 Induction and Xeno‐Sensing Receptors Pregnane X Receptor, Constitutive Androstane Receptor, Aryl Hydrocarbon Receptor and Peroxisome Proliferator‐Activated Receptor α at the Crossroads of Toxicokinetics and Toxicodynamics. (29th April 2018) - Hakkola, Jukka; Bernasconi, Camilla; Coecke, Sandra; Richert, Lysiane; Andersson, Tommy B.; Pelkonen, Olavi
Abstract: Pregnane X receptor (PXR), constitutive androstane receptor (CAR), aryl hydrocarbon receptor (AHR) and peroxisome proliferator‐activated receptor α (PPARα) are ligand‐activated transcription factors that regulate expression of many xenobiotic‐metabolizing enzymes including several cytochrome P450 (CYP) enzymes. Many xenobiotics induce CYP enzymes through these intracellular receptors and consequently affect toxicokinetics and possible metabolic activation of the receptor ligands and other xenobiotics utilizing similar metabolic pathways. However, it is now apparent that the xenobiotic receptors regulate also many endogenous functions and signalling pathways, and xenobiotic exposure thus may dysregulate an array of fundamental cell functions. This MiniReview surveys and discusses the multifaceted roles of xenobiotic receptors, for which CYP induction may serve as the first alert and possibly a biomarker for exposure to xenobiotics. With the current emergence of the adverse outcome pathway (AOP) concept, these receptors are being and will be assigned as molecular initiating events or key events in numerous discrete toxicity pathways.